Mechanistic insights into the detection of free fatty and bile acids by ileal glucagon-like peptide-1 secreting cells - Deborah A. Goldspink; Van B. Lu; Lawrence J. Billing; Pierre Larraufie; Gwen Tolhurst; Fiona M. Gribble; Frank Reimann (Elsevier, 2018)
Objectives: The aim of this study was to investigate the electrical properties of ileal Glucagon-like peptide 1 (GLP-1) secreting L-cells using murine organoid cultures and the electrophysiological and intracellular signaling pathways recruited following activation of the Gαq-coupled free fatty acid receptors FFA1 and Gαs-coupled bile acid receptors GPBAR1. Methods: Experiments were performed using ileal organoids generated from mice transgenically expressing fluorescent reporters (Epac2-camps and GCaMP3) under control of the proglucagon promoter. Electrophysiology and single cell imaging were performed on identified L-cells in organoids, and GLP-1 secretion from cultured organoids was measured by immunoassay. Results: The FFA1 ligand TAK-875 triggered L-cell electrical activity, increased intracellular calcium, and activated a depolarizing current that was blocked by the TRPC3 inhibitor Pyr3. TAK-875 triggered GLP-1 secretion was Pyr3 sensitive, suggesting that the TRPC3 channel links FFA1 activation to calcium elevation and GLP-1 release in L-cells. GPBAR1 agonist triggered PKA-dependent L-type Ca2+ current activation and action potential firing in L-cells. The combination of TAK-875 and a GPBAR1 agonist triggered synergistic calcium elevation and GLP-1 secretory responses. Conclusions: FFA1 and GPBAR1 activation individually increased electrical activity in L-cells by recruiting pathways that include activation of TRPC3 and L-type voltage-gated Ca2+ channels. Synergy between the pathways activated downstream of these receptors was observed both at the level of Ca2+ elevation and GLP-1 secretion. Keywords: GLP-1, FFA1, GPBAR1, Organoid, Diabetes, Obesity